Фотокаталітична деградація метиленового блакитного за участю ZnО-вмісних шаруватих подвійних гідроксидів та їх похідних - Starukh, G. M.; Oranska, O. I.; Linnik, O. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
Zn-Al layered double hydroxides with Zn:Al ratio 2:1, 3:1, 4:1 have been synthesized by coprecipitation method. Their perspectivity for the photocatalytic degradation of organic dyes have been studied. The influence of Zn:Al ratio in layered double hydroxides, the treatment temperature and the ability to restore the layered structure on the photocatalytic activity of the mixed oxides obtained by decomposition thermal destruction of layered double hydroxides in degradation of model dye methylene blue have been found.